2022
DOI: 10.3389/fpubh.2022.771190
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Knowledge, Attitude and Practice Toward Needle Stick Injury Among Health Care Workers in Abha City, Saudi Arabia

Abstract: BackgroundA needle stick injury is a serious occupational health hazard in health care settings. Health care workers are at risk of bloodborne diseases and the psychological consequences of these injuries. This study aims to estimate the incidence of needle stick injuries among healthcare workers during the previous 12 months and to assess their knowledge, attitude, and practice toward these injuries.MethodsThis cross-sectional study was conducted from 1st August 2019 till 15th February 2020, and included 786 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 43 publications
7
26
4
1
Order By: Relevance
“…In this study, the prevalence of sharp injuries was highest in nurses (47.3%), similar to several other studies in Dessie (17) , in Saudi Arabia (1) , and Dire Dawa, Ethiopia (7) , Northwestern Ethiopia (6) , Western Wollega (4) . It could be because nurses administer most of the injections and are responsible for intravenous fluid administration and other procedures which require the use of needles and other sharp devices.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this study, the prevalence of sharp injuries was highest in nurses (47.3%), similar to several other studies in Dessie (17) , in Saudi Arabia (1) , and Dire Dawa, Ethiopia (7) , Northwestern Ethiopia (6) , Western Wollega (4) . It could be because nurses administer most of the injections and are responsible for intravenous fluid administration and other procedures which require the use of needles and other sharp devices.…”
Section: Discussionsupporting
confidence: 91%
“…Also, the insufficient number of nurses and medical devices at workplaces, distraction at work, heavy workload, poor organization, multiple or repeated attempts to complete a procedure, and spending more time in direct patient contact may have increased their vulnerability to such injuries. The current study found that 67% of the study subjects recapped needles after use, which was an important cause of sharp injuries, as observed in several other studies (1,4,7,14) .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations